SENTRIPETAL AGAMA : SINERGI KEPOLISIAN DAN KEMENTERIAN AGAMA DALAM PENCEGAHAN TERORISME DI WONOGIRI - Ruslina Dwi Wahyuni (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2022)
Abstract: this research was conducted to see the influence of the role of the Police and the Ministry of Religion on the efforts to prevent terrorism through religious centripetals. The method used is descriptive quantitative with data collection techniques through questionnaires and technical data analysis with path analysis (Path Analysis). The findings in this study are that the role of the police and the ministry of religion does not directly affect terrorism prevention, but indirectly has a significant effect on terrorism prevention through religious centripetals. So religion as a centripetal needs to be treated properly in order to maintain unity so that efforts to prevent terrorism can continue to be carried out.  Keywords : terrorism, religious centripetal, police, ministry of religion